Maintaining quality of software engineering education by a shared repository of course materials in a multilateral setting - Bothe, Klaus; Budimac, Zoran; Putnik, Zoran; Ivanovic, Mirjana; Stoyanov, Stanimir; Stoyanova-Doyceva, Asya; Zdravkova, Katerina; Jakimovski, Boro; Jurca, Ioan; Nocovic, Novica; Kalpic, Damir; Cico, Betim (IEEE, 2014)
Developing teaching materials is a time-consuming and expensive activity. Thus, over the years, several consortia have created joint materials to benefit from them. It is expected that shared teaching materials are a means to save effort in its development, to transfer methodological and technical knowledge between different university staff, and to exchange experience in practical application. However, does it really pay off considering the diversity of different educational environments and the difficulties of using externally produced materials, rather than dedicated individual ones? This paper reports on the experience gained in a multi-country project. Both success factors and problems are outlined. It turned out that sharing an educational repository by several partners supports maintaining quality of teaching materials by joint efforts and distributed contributions.
Keywords: Software engineering; shared teaching materials; multilateral co-operation